Urinary stone composition: Gender and age variations, and evolution in the last 7 years. - Valente, Pedro (2017)
Objectives: To evaluate urinary stone composition in our institution, its gender and age, including variations and the evolution in the last 7 years. Material and Methods: The authors reviewed all urinary stone analysis performed since January 2009 to September 2015 in our hospital – Centro Hospitalar do Tâmega e Sousa, Penafiel, Portugal. Patients were stratified by gender, age and stone composition analyzing the evolution of stone composition in different years. The stone analysis method was infrared spectroscopy. Results: From 302 valid stone analysis reports, 55,3% were female and 44,7% were male patients. Mean patient age was 51±14 years old. A total of 7 different mineral components were identified. 51,6% (n=156) of all the stones had Calcium Oxalate, 41% (n=124) had Calcium Phosphate (33% of Apatite form), 37,7% (n=114) had Uric Acid, 22,1% (n=67) had Ammonium Urate, 9,6% (n=29) had Magnesium Ammonium Phosphate, 6,3% (n=19) had Sodium Urate, and 1,3% (n=4) had Cystine in its composition. Only 30,4% of stones had a single chemical compound. Of these 56% were pure stones of Calcium Oxalate, and 31% were pure stone of Uric Acid. The most frequent mixed stone was Calcium Oxalate + Calcium Phosphate (Apatite) followed by Uric Acid + Ammonium Urate comprehending 45% and 27% of all mixed stones respectively. Related to the ethology we divided stones into 3 groups, pure non-infection, pure infection, and mixed with component of infection, and the prevalence was 37,7%, 4,3% and 57,9% respectively. The distribution between genders was similar and the highest difference was in the Ammonium Urate compound with 28% prevalence in male and 17% in women. (p=0,379) Patients after 50 years old had more prevalence of Uric Acid component accounting for 49% of their stones.(p<0,001) . Along the 7 years of study we identified a significant reduction in the prevalence of mixed stones with component of infection, gradually decreasing from 89,6% in 2009 to 27% in 2015. Conclusions: Calcium Oxalate calculus were the most prevalent, but this difference was not as important as in other studies worldwide. This study highlights the importance of the development of National and European database to report all regional stone composition variations.